2020
DOI: 10.1007/s00425-020-03346-w
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into expansion and functional diversification of MIR169 family in tomato

Abstract: Expansion of MIR169 members by duplication and new mature forms, acquisition of new promoters, differential precursor-miRNA processivity and engaging novel targets increases the functional diversification of MIR169 in tomato. (29/30

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 92 publications
1
22
0
Order By: Relevance
“…Diamonds, ellipses, and arrowheads represent the KEGG pathways, target genes, and miRNAs, respectively. Luan et al, 2015;Hanemian et al, 2016;Du et al, 2017;Li et al, 2017;Serivichyaswat et al, 2017;Rao et al, 2020). However, to the best of our knowledge, there are no reports describing the involvement of miR169 in the male sterility of soybean or other plant species.…”
Section: Mir169 May Regulate Pollen Development In Cytoplasmic Male Sterile Soybeanmentioning
confidence: 98%
“…Diamonds, ellipses, and arrowheads represent the KEGG pathways, target genes, and miRNAs, respectively. Luan et al, 2015;Hanemian et al, 2016;Du et al, 2017;Li et al, 2017;Serivichyaswat et al, 2017;Rao et al, 2020). However, to the best of our knowledge, there are no reports describing the involvement of miR169 in the male sterility of soybean or other plant species.…”
Section: Mir169 May Regulate Pollen Development In Cytoplasmic Male Sterile Soybeanmentioning
confidence: 98%
“…The researchers also reported that the over-expression of GmNF-YA3 in Arabidopsis resulted in increased sensitivity to salinity and ABA stresses [40]. Tomato miR169 overexpression lines induced drought stress through its four targets NF-YA1/2/3 and multidrug resistance-associated protein gene 1 (MRP1), which were all down-regulated [42]. Constitutive over-expression of tomato miR169c improved drought stress tolerance as compared to wild-type plants through reduction of leaf water loss, the stomatal opening, and transpiration rate [42].…”
Section: Mirnas In Abiotic Stress Tolerancementioning
confidence: 99%
“…Tomato miR169 overexpression lines induced drought stress through its four targets NF-YA1/2/3 and multidrug resistance-associated protein gene 1 (MRP1), which were all down-regulated [42]. Constitutive over-expression of tomato miR169c improved drought stress tolerance as compared to wild-type plants through reduction of leaf water loss, the stomatal opening, and transpiration rate [42]. The Agrostis stolonifera plants overexpressing a miR319 rice gene Osa-miR319a, increased their wax contents in leaves for the retention of water and reduced their Na + ion uptake.…”
Section: Mirnas In Abiotic Stress Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…The miR169 family is evolutionarily conserved and reported in several plant species (Guo et al 2020;Sunkar and Jagadeeswaran 2008). In addition, miR169 has also been shown to regulate several developmental, abiotic and biotic stress response pathways, including cold stress (Du et al 2017;Li et al 2008;Lee et al 2010;Rao et al 2020;Song et al 2018;Yu et al 2019;Zhao et al 2011, Zhou et al 2008. miR169 family targets NUCLEAR FACTOR Y (NF-YA), a heterotrimeric transcription factor composed of NF-YA, NF-YB and NF-YC proteins ( Ni et al 2013, Petroni et al 2012.…”
Section: Mir169-nf-ya Module Is Altered In Slr1 Under Low Temperaturementioning
confidence: 99%